Cynicism as a Fundamental Dimension of Moral Decision-Making: A Scale Development - Turner, James H. (Journal of business ethics, 2001)
Altruism and cynicism are two fundamental algorithms of moral decision-making. This derives from the evolution of cooperative behavior and reciprocal altruism and the need to avoid being taken advantage of. Rushton (1986) developed a self-report scale to measure altruism, however no scale to measure cynicism has been developed for use in ethics research. Following a discussion of reciprocal altruism and cynicism, this article presents an 11-item self-report scale to measure cynicism, developed and validated using a sample of 271 customer-service and sales personnel.